Design and Implementation of Portable Vibration Analysis and Diagnosis System - Najem, Saleh I.; Ali, Jaafar Kh.; Ali, AbdelBaki Kh.; AbdelAali, Ali Hassan (Basrah Journal for Engineering Sciences, 2012)
In this work, a portable vibration analysis and diagnosis system is designed and constructed. The system is capable of doing most of the known analysis techniques such as FFT, time waveform, cepstrum analysis, dual channel analysis, orbit, envelope detection and other techniques. Furthermore, a new fast and efficient tracking analysis algorithm, suitable for portable instruments, has been proposed. This technique provides the data required to get accurate Bode and Nyquist plots for diagnostic analysis during machine run-up and coast-down tests. Moreover, FFT waterfall and spectrogram techniques have been included. Also, single-plane and dual-plane field balancing have been implemented in this system to execute field balancing tasks.